2020
DOI: 10.1128/msphere.00928-20
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Characterization of the Babesia divergens Asexual Life Cycle, from the Trophozoite to the Multiparasite Stage

Abstract: Babesia is an apicomplexan parasite of significance that causes the disease known as babesiosis in domestic and wild animals and in humans worldwide. Babesia infects vertebrate hosts and reproduces asexually by a form of binary fission within erythrocytes/red blood cells (RBCs), yielding a complex pleomorphic population of intraerythrocytic parasites. Seven of them, clearly visible in human RBCs infected with Babesia divergens, are considered the main forms and named single, double, and quadruple trophozoites,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cryo-SXT can provide understanding of the spatial organization of the different cellular organelles during the infection, but to achieve a better comprehension of the complexity of virus-host interactions, it is recommended to combine cryo-SXT data with other imaging techniques that can provide the precise localization or the higher resolution structure of the particular viral or host factors being studied. Correlative workflows combining cryo-SXT with techniques such as cryo-ET, visible light fluorescence microscopy, hard X-ray fluorescence tomography or numerical simulations have already proven their potential in several multi-length scale structural studies [24,[43][44][45][46][75][76][77]. A particularly powerful approach is a correlative cryo-imaging pipeline, in which the same sample is imaged with super-resolution 3D structured illumination fluorescence microscopy (cryo-SIM) and with cryo-SXT, allowing for a comprehensive view of both cellular ultrastructure and the related molecular organization over extended cellular volumes [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Cryo-SXT can provide understanding of the spatial organization of the different cellular organelles during the infection, but to achieve a better comprehension of the complexity of virus-host interactions, it is recommended to combine cryo-SXT data with other imaging techniques that can provide the precise localization or the higher resolution structure of the particular viral or host factors being studied. Correlative workflows combining cryo-SXT with techniques such as cryo-ET, visible light fluorescence microscopy, hard X-ray fluorescence tomography or numerical simulations have already proven their potential in several multi-length scale structural studies [24,[43][44][45][46][75][76][77]. A particularly powerful approach is a correlative cryo-imaging pipeline, in which the same sample is imaged with super-resolution 3D structured illumination fluorescence microscopy (cryo-SIM) and with cryo-SXT, allowing for a comprehensive view of both cellular ultrastructure and the related molecular organization over extended cellular volumes [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…In B. microti-the basal piroplasmid species (Babesia microti-like group)-the obscure coiled structure that protrudes from the parasite into the host cytoplasm has been observed and speculated to contain digestive enzymes. Similarly, possible haemoglobin-containing vesicles were also observed from B. divergens trophozoites, indicating-yet not confirming-the endocytic uptake of hemoglobin from the cytoplasm of host erythrocytes [47]. The role of hemoglobin invaginations in trophozoites of different species of Babesia remains unclear, but could be relevant to the biology of piroplasms, e.g., by limited digestion of hemoglobin providing the essential source of heme to these heme auxotrophic organisms.…”
Section: Expression Profiling Of Bmasps Indicate Their Various Roles Throughout the Life Cycle Of Babesia Microtimentioning
confidence: 97%
“…In contrast, B. divergens has a much more complex replicative cycle (55). Indeed, conflicting literature exists suggesting the replication cycle varies from 4-12 hr, however in most cases it appears the minimal time for division is between 4-5 hr (55,105,106). Of these, only a single study was conducted on synchronous parasites (55).…”
Section: Interactive Web-appmentioning
confidence: 99%
“…Subsequent division cycles are possible in B. divergens and the timing of these cycles can vary between 9-14 hr (55). In all studies of the dynamics of B. divergens division dynamics, there is a significant range of time for a single division, highlighting the difficulty in generating an exact measurement (55,105,106). This variability leads to difficulty in synchronizing Babesia parasites, which currently relies on mechanical release of parasites from RBCs using filtration (55, 56), and we have recently shown that parasites may be egress competent at various times in their intraerythrocytic development (37).…”
Section: Interactive Web-appmentioning
confidence: 99%